Nitrification under the influence of long-term fertilizer application in a tropical vertisol. Issue 4 (21st March 2022) - Mohanty, Santosh Ranjan; Parihar, Manoj; Dubey, Garima; Parmar, Rakesh; Jain, Devendra; Singh, Muneshwar; Patra, Ashok; Chaudhari, Suresh Kumar; Kollah, Bharati
ABSTRACT: The current experiment envisages estimating nitrification and elucidates the mechanistic processes of nitrogen mineralization in a long-term fertilizer experiment (LTFE) on a soybean-wheat cropping system. The experiment had four treatments: fallow (no fertilizer and no crop), control (no fertilizer), inorganic (recommended dose as 100% NPK), and integrated (100% NPK + farmyard manure FYM). The potential nitrification rate (PNR) estimated as µg NO3 − produced g −1 soil d −1 was 0.88 in fallow, 1.86 in control, 1.278 in 100% NPK, and 1.493 in 100% NPK + FYM. Real-time PCR quantification of bacterial amoA gene (× 10 4 amoA gene copies g −1 soil) was 19.33 in fallow, 43.33 in control, 30.33 in 100% NPK, and 29.33 in 100% NPK + FYM. The amoA gene copies (x 10 4 gene copies g −1 soil) of archaea ranged from 11.67 to 38.67. The X-ray diffraction (XRD) of soils indicated that the intensity of the NH4 + minerals was highest in control and lowest in fallow. Soybean grain and biomass yields were highest in 100% NPK + FYM and lowest in control. The study highlights that continuous cropping without fertilizer may alter soil microbial metabolism for the acquisition of nitrogen from mineralization of readily unavailable mineral fractions.